Formulasi Hand Sanitizer dari Ekstrak Biji Pangi (Pangium edule Reinw) - Rohana, Rohana; Stevani, Hendra; Dewi, Ratnasari (Media Farmasi XXX, 2019)
Pangi seeds contain flavonoids and are proven to have an antibacterial effect, though they are still used in a traditional way within the community. There is a need for it to be developed into a formula that is more practical and durable, such as Hand sanitizer. The purpose of this research is to formulate the preparation of Hand sanitizer from Pangi Seed Extract (Pangium edule Reinw). The seeds were extracted by maceration using distilled water and made into Hand sanitizer gel using TEA, Glycerin, Nipagin, and Aquades. The variations in the concentration of carbohydrate and sodium CMC base were 0.25%: 2%; 0.5%: 3%; 0.75%: 4%. The results showed that all three preparations before and after storage were homogeneous, pale yellow, and odorless. Besides, the viscosity of the gel ranges from 242471-4151 cP, but changes after storage. However, gel pH ranges from 5-6 and does not change after storage. In all the three preparations, no synergy occurred, and their spreadability ranged from 5cm to 7.5cm, undergoing changes after storage. This study concludes that the Pangi Seed extract might be formulated into a gel preparation with a Carbopol: Sodium CMC base concentration of 0.5%: 3% and meets all quality requirements.Keywords: Pangi Seed, Gel, Carbopol, Na. CMC, Hand sanitizer.Biji Pangi mengandung flavonoid serta terbukti memiliki efek antibakteri, namun penggunaannya oleh masyarakat masih secara tradisional sehingga perlu dikembangkan menjadi formula yang lebih praktis digunakan, dan lebih tahan lama seperti Hand sanitizer. Tujuan penelitian untuk memformulasikan sediaan Hand sanitizer dari ekstrak Biji Pangi (Pangium edule Reinw). Biji Pangi diekstraksi dengan cara maserasi menggunakan pelarut akuades dan dibuat menjadi gel Hand sanitizer menggunakan TEA, Gliserin, Nipagin, Akuades serta variasi konsentrasi basis Karbopol dan Natrium CMC yaitu 0,25%:2% ; 0,5%:3% ; 0,75%:4%. Hasil penelitian menunjukkan ketiga sediaan sebelum dan setelah penyimpanan homogen, berwarna kuning pucat, dan tidak berbau. Kekentalan gel berkisar`2471-4151 cP, tapi mengalami perubahan setelah penyimpanan. pH gel berkisar 5-6, tidak berubah setelah penyimpanan. Tidak terjadi sineresi pada ketiga sediaan. Daya sebar ketiga sediaan berkisar 5cm-7,5cm, mengalami perubahan setelah penyimpanan. Dari penelitian ini dapat disimpulkan bahwa ekstrak Biji Pangi dapat diformulasikan menjadi sediaan gel dengan konsentrasi basis Karbopol: Natrium CMC yaitu 0,5% : 3% dan memenuhi semua persyaratan mutu.Kata Kunci : Biji Pangi, Gel, Karbopol, Na. CMC, Hand sanitizer.